The Effect of Microwave Oven Power Variations on Co-Pyrolysis Process of Oil Palm Shells and Polystyrene: Pengaruh Variasi Daya Microwave Oven Terhadap Proses Co-Pirolisis Cangkang Kelapa Sawit dan Polistirena - Nazarrudin, Rizal; Saptoadi, Harwin (Universitas Muhammadiyah Sidoarjo, 2022)
Indonesia has a very large area of ​​oil palm plantations, one of which is the island of Sumatra. However, in processing and handling palm oil product waste in the form of palm shells, it has not been maximized. Therefore, the chemical decomposition process can play an important role in supporting waste management and sustainable energy use in Indonesia which is not yet optimal. In this research, the proper use of power will be tested with the help of microwaves as a reactor for the co-pyrolysis process of oil palm shells and polystyrene plastic. The purpose of this study was to determine the appropriate power to produce maximum co-pyrolysis products and to investigate the physical characteristics of the oil-pyrolytic products. The test uses a microwave oven which has a power variation of 300 W, 450 W, 600 W, and 800 W with the addition of a catalyst. The ratio of the composition of oil palm shells to polystyrene plastic is 1:1 with a total mass of 105 gr and using coconut shell charcoal as an activated carbon absorber. The pyrolysis temperature is 500 ℃, the nitrogen gas flow rate is 1.5 LPM, and the pyrolysis time is 60 minutes. Furthermore, testing the physical properties of the pyrolysis oil product in the form of density, acidity, and viscosity testing. The results showed that the optimal power to obtain oil-pyrolytic was 600 W with a product oil of 17.6%, and from the physical properties it had a low viscosity value of 2.55 mPa.s with a pH level of 6.6.